(untitled) (Research, Society and Development, 2022)
Objective: to understand the organization of care for mental health demands, focusing on psychological distress, in a Basic Health Unit (UBS) in a small town in the state of Santa Catarina. Methods: data were collected through focus groups, audio-recorded, with 3 teams of Family health Strategies from a UBS located in that city. Data were treated using Bardin’s Content Analusis and the results condensed into a category. Results: it was found that mental health in the analyzed UBS is closely related to pathologies and diagnoses to the detriment of the subject and his uniqueness, valuing care actions based on the conduct complaint and which result in the remission of symptoms from the health framework mental into an ideal of normality. The physican is seen as the center of the clinic, to the detriment of interprofessional work, which includes the use of hard and light hard care technologies, such as medications and diagnoses, disregarding the use of light technologies such as welcoming, listening and bonding. Final considerations: Thus, it appears that the actions of mental health care in the analyzed UBS are allied to the parameters of a traditional clinic.